Revolutionizing Dental Health Care: An In-Depth Exploration of Technological Advancements - Bharadwaj, R. Sumukh; Kalgeri, Sowmya Halasabalu; Shivakumar, Ashwini Tumkur; Doddawad, Vidya; Shankar, Parinitha Mysore; B., Sunil Kumar B. (European Journal of General Dentistry, 2024)
The present scenario caused by the coronavirus disease 2019 pandemic—and the recession in the dental industry—a newer approach modality is on every dentist's mind. As the future is always questionable in the present situation, we can expect remarkable changes in the dental field, which will revolutionize dental health care facilities worldwide. Several upcoming trends are introduced every year. Recent studies demonstrate that in the future dental field will be presented with exciting new technologies, improved business practices, and novel ways to optimize patient experience, and even nanorobotic dentistry will be in practice.Future dentistry is expected to have more innovation as it is adopting the latest technologies and facilitating the growth of global dentistry. This is because the increasing frequency of the treatment of dental disorders and related risk factors, combined with the introduction of advanced technology will be some of the major factors driving technological growth over the next few years.This article communicates the newer changes taking place in dentistry which will have an impact on the future dental field.
Keywords: artificial intelligence; augmented reality; bioprinting; camera; dentistry; laser; technology; 3D printing